Effects of Probiotic (Lactobacillus spp) Mixed with Cassava Leaves (Manihot esculenta) on Growth Performances and Meat Quality of Cherry Valley Duck (Anas platyrhynchos domesticus) - Conniey, Fay Komilus; Nur Al Syifaa, Hassan (Penerbit Universiti Sultan Zainal Abidin, 2020)
Probiotics are beneficial bacteria that had been used in poultry industry as alternative sources for antibiotic. The aim of this study was to determine the effect of probiotic mixed with cassava leaves (Manihot esculenta) on Cherry Valley Duck (Anas platyrhynchos domesticus) growth performance, carcass characteristics and meat quality. Lactobacillus spp. was used in this experiment to see its effectiveness in enhancing quality of cassava leaves as potential feed towards optimum growth performance of ducks like body weight gain, feed intake and feed conversion ratio, carcass characteristics and meat quality. 34 tails of Cherry Valley ducks aged 14 days with average weight of 500 g were randomly assigned to four treatments in triplicates. Treatments for the 35 days feeding trial were T1 at 0% probiotic + 75% commercial diet + 25% cassava leaves (control), T2 (0.15% probiotic + 75% commercial diet + 25% cassava leaves), T3 (0.30% probiotic + 75% commercial diet + 25% cassava leaves) and T4 (0.45% probiotic + 75% commercial diet + 25% cassava leaves) respectively. Proximate analysis was also conducted to determine nutritional content like protein, lipid, moisture, ash and fiber. Results show that supplementation of probiotic at 0.15% Lactobacillus spp. into 25% of cassava leaves and 75% commercial pellet gave highest body weight gain (BWG), low feed conversion ratio (FCR), highest carcass yield and good meat quality. It can be concluded that inclusion of probiotic at 0.15% in cassava leaves as duck’s diet gives good growth performance and may become an alternative super diet for duck in future.